A History of Parliamentary Elections and Electioneering in the Old Days : Showing the State of Political Parties and Party Warfare at the Hustings and in the House of Commons from the Stuarts to Queen Victoria - Grego, Joseph, 1843-1908 (Salt Lake City, UT : Project Gutenberg, 2016)
"A History of Parliamentary Elections and Electioneering in the Old Days" by Joseph Grego is a historical account written in the late 19th century. This work explores the evolution of parliamentary elections and the various methods of electioneering in Britain from the time of the Stuarts to the reign of Queen Victoria. The text likely examines the intricate relationships between social classes, political parties, and the electoral process, centering on themes of corruption, representation, and civic engagement. The opening of the book delves into the origins of parliamentary assemblies and the complex rules governing elections, starting from early medieval practices to the formalization of the House of Commons. It highlights the role of key figures and evolving practices, touching upon concepts such as electoral qualifications, bribery, and the increasing power dynamics in electioneering. Grego establishes a historical context that underpins the development of Britain's parliamentary system, setting the stage for the ensuing chapters that promise to detail the vivid and often tumultuous political landscape of earlier centuries. (This is an automatically generated summary.)
Release date is 2016-05-24
E-text prepared by MWS, Wayne Hammond, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (https://archive.org/details/americana)
Keywords: Great Britain -- Politics and government; Great Britain. Parliament -- Election